Patient-centered drug delivery and its potential applications for unmet medical needs. (August 2017) - Park, Chulhun; Meghani, Nilesh M; Amin, Hardik H; Nguyen, Van Hong; Lee, Beom-Jin
Pharmaceutical dosage forms address diverse key components but satisfying unmet patient needs to enhance patient adherence is a major challenge. The desired design of patient-centered drug products should be based on characteristics of various components, such as patients, disease, routes of administration, drug delivery technologies and active pharmaceutical ingredients. Understanding of targeting patients and their physiological and biological environments is pivotal for developing suitable patient-centered drug products. In this review, key components of an ideal drug delivery system were considered. Then, stepwise approaches for designing patient-centered drug products were suggested. Finally, various case studies are also presented and considered to develop models of patient-centered drug products.